2003
DOI: 10.1289/ehp.6164
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of benzene-induced hematotoxicity and leukemogenicity: cDNA microarray analyses using mouse bone marrow tissue.

Abstract: Although the mechanisms underlying benzene-induced toxicity and leukemogenicity are not yet fully understood, they are likely to be complicated by various pathways, including those of metabolism, growth factor regulation, oxidative stress, DNA damage, cell cycle regulation, and programmed cell death. With this as a background, we performed cDNA microarray analyses on mouse bone marrow tissue during and after a 2-week benzene exposure by inhalation. Our goal was to clarify the mechanisms underlying the hematoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 56 publications
0
34
1
1
Order By: Relevance
“…Among reactions to hydroquinone exposure, we found that DNA damage repair activity and responsiveness to cell death were altered in Fhit-deficient cells, alterations that could contribute to an increase in genomic instability during hematopoiesis. Considering that the DNA damage checkpoint pathway can induce immediate suppression of cell cycling of hemopoietic progenitors and prominent suppression of hemopoiesis, it has been proposed that the process of recovery from intermittent benzeneinduced marrow suppression may be involved in benzene-induced leukemogenesis (8). Further study would include assessment of oscillatory changes in ROS, possibly associated with chromosome aberrations in hematopoietic disorders or in transplanted bone marrow cells, after exposure to genotoxin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among reactions to hydroquinone exposure, we found that DNA damage repair activity and responsiveness to cell death were altered in Fhit-deficient cells, alterations that could contribute to an increase in genomic instability during hematopoiesis. Considering that the DNA damage checkpoint pathway can induce immediate suppression of cell cycling of hemopoietic progenitors and prominent suppression of hemopoiesis, it has been proposed that the process of recovery from intermittent benzeneinduced marrow suppression may be involved in benzene-induced leukemogenesis (8). Further study would include assessment of oscillatory changes in ROS, possibly associated with chromosome aberrations in hematopoietic disorders or in transplanted bone marrow cells, after exposure to genotoxin.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative gene expression profiling of p53 knockout and wild-type (Wt) mice has revealed altered expression of cell cycle, apoptosis, and growth control genes in hematopoietic samples from benzene-exposed mice, indicating that benzene exposure activates checkpoint proteins such as p21 and p53 (8,9), which inhibit DNA replication and apoptosis (10,11). Recent studies indicate that p21 cooperates with Chk1 to prevent apoptosis during DNA replication fork stress, which is important for maintaining chromosome stability (11).…”
Section: Introductionmentioning
confidence: 99%
“…2 Although the mechanisms underlying benzene-induced toxicity and leukemogenicity are not yet fully understood, they are likely to be complicated by various pathways, including those of metabolism, growth factor regulation, oxidative stress, DNA damage, cell cycle regulation, and programmed cell death. 3 The potential metabolic mechanisms underlying the hemopoietic toxicity of benzene include bioactivation of phenolic metabolites of benzene by myeloperoxidases in the bone marrow and ring opening reactions to generate muconate derivatives. 4 This study is aimed at the knowledge on the correlation between the urine trans, trans-muconic acid (tt-MA), a novel biomarker for accumulated uptake of benzene, 5 and myelopeozidase index (MPXI) in the subjects occupationally exposed to benzene.…”
Section: To the Editormentioning
confidence: 99%
“…Epidemiological studies have shown that exposure to benzene results in an increased risk of aplastic anemia, myelodysplastic syndromes, leukemia, and other blood disorders (Goldstein, 1988). Benzene metabolites may induce toxicity and leukemogenicity by oxidative stress, DNA damage, growth factor regulation, cell cycle regulation, and/or programmed cell death (Yoon et al, 2003).…”
Section: Introductionmentioning
confidence: 99%